Gut-liver axis: Pathophysiological concepts and clinical implications - Tilg, Herbert; Adolph, Timon E.; Trauner, Michael (Cell metabolism, 2022)
Bidirectional crosstalk along the gut-liver axis controls gastrointestinal health and disease and exploits environmental and host mediators. Nutrients, microbial antigens, metabolites, and bile acids regulate metabolism and immune responses in the gut and liver, which reciprocally shape microbial community structure and function. Perturbation of such host-microbe interactions is observed in a variety of experimental liver diseases and is facilitated by an impaired intestinal barrier, which is fueling hepatic inflammation and disease progression. Clinical evidence describes perturbation of the gut-liver crosstalk in non-alcoholic fatty liver disease, alcoholic liver disease, and primary sclerosing cholangitis. In liver cirrhosis, a common sequela of these diseases, the intestinal microbiota and microbial pathogen-associated molecular patterns constitute liver inflammation and clinical complications, such as hepatic encephalopathy. Understanding the intricate metabolic interplay between the gut and liver in health and disease opens an avenue for targeted therapies in the future, which is probed in controlled clinical trials. Tilg et al. discuss experimental and clinical aspects of the bidirectional gut-liver crosstalk in health and how perturbation of such inter-organ communication promotes liver diseases. Collectively, the diet, gut mucosal immunity and related microbial commensalism, and hepatic metabolism shape the communication along the gut-liver axis, fueling various liver diseases.